Substance use service availability in HIV treatment programs: Data from the global IeDEA consortium, 2014-2015 and 2017. - Angela M Parcesepe; Kathryn Lancaster; E Jennifer Edelman; Raquel DeBoni; Jeremy Ross; Lukoye Atwoli; Mpho Tlali; Keri Althoff; Judicaël Tine; Stephany N Duda; C William Wester; Denis Nash; et al. (PLoS ONE)
Background Substance use is common among people living with HIV and has been associated with suboptimal HIV treatment outcomes. Integrating substance use services into HIV care is a promising strategy to improve patient outcomes. Methods We report on substance use education, screening, and referral practices from two surveys of HIV care and treatment sites participating in the International epidemiology Databases to Evaluate AIDS (IeDEA) consortium. HIV care and treatment sites participating in IeDEA are primarily public-sector health facilities and include both academic and community-based hospitals and health facilities. A total of 286 sites in 45 countries participated in the 2014-2015 survey and 237 sites in 44 countries participated in the 2017 survey. We compared changes over time for 147 sites that participated in both surveys. Results In 2014-2015, most sites (75%) reported providing substance use-related education on-site (i.e., at the HIV clinic or the same health facility). Approximately half reported on-site screening for substance use (52%) or referrals for substance use treatment (51%). In 2017, the proportion of sites providing on-site substance use-related education, screening, or referrals increased by 9%, 16%, and 8%, respectively. In 2017, on-site substance use screening and referral were most commonly reported at sites serving only adults (compared to only children/adolescents or adults and children/adolescents; screening: 86%, 37%, and 59%, respectively; referral: 76%, 47%, and 46%, respectively) and at sites in high-income countries (compared to upper middle income, lower middle income or low-income countries; screening: 89%, 76%, 68%, and 45%, respectively; referral: 82%, 71%, 57%, and 34%, respectively). Conclusion Although there have been increases in the proportion of sites reporting substance use education, screening, and referral services across IeDEA sites, gaps persist in the integration of substance use services into HIV care, particularly in relation to screening and referral practices, with reduced availability for children/adolescents and those receiving care within resource-constrained settings.